The Effect of Apyrase on Platelet Retention in Normal Subjects and in Patients with Abnormal Cardiac Valves or with von Willebrand’s Disease - Rifkin, Paul L.; Friedberg, Neal M.; Zucker, Marjorie B. (Thrombosis and Haemostasis, 1973)
Earlier studies showed that platelet retention was low in disturbed blood and was restored by incubating the blood with apyrase. The low values appeared to be due to ADP-induced inhibition. Patients with von Willebrand’s disease and some patients with cardiac valve abnormalities or prostheses had reduced platelet retention in glass bead columns. Although retention was often increased by incubating the blood with apyrase, it never reached normal values. Retention in normal blood was low when short columns were used and was also increased by apyrase. Thus, ADP-induced inhibition is apparently present even in carefully drawn blood and is probably not responsible for the poor retention in von Willebrand’s disease and cardiac valve abnormalities.